Levede Poul Helgesen endnu længe efter reformationen? Om forfatterskabet til den bevarede fortale til en tabt Luther-bog fra 1544 - Sjøberg, Erik (Kirkehistoriske Samlinger, 2009)
Poul Helgesen still living a long time after the Reformation? About the authorship ofthe preserved preface to a lost bookfrom 1544 with extractsfrom many Works of Luther The thesis of this article is that the author ofthe preserved preface to a (now lost) book from 1544 with extracts from many of Luther’s books is the Carmelite friar Poul Helgesen (Paulus Helie). To-day the gene- rally accepted view among historians and church historians is that Poul Helgesen died c. 1535. The present article is meant as an introduction to a discussion of my thesis. I argue in favour of my thesis by comparing the contents and the language in the preface with thoughts and opinions, style and language, in books written by Poul Helgesen. The preface is written in the name ofthe canons of Lund and is addressed to all Christian readers, especially to King Christian the Third. According to the king’s wishes the theological professors at the University of Copenhagen in 1543 formulated three theses - about the Lutheran views ofthe Mass, the Lord’s Supper and the Benefice. The theses were meant to be discussed publicly between the Lutheran professors and the Catholic canons from the chapters of Copenhagen, Roskilde, and Lund and finally be accepted by the canons. Apparently the canons in Lund with their Luther book and its preface hoped to avoid the planned theological disputation in Copenhagen. In 1543 the Lutheran university teachers debated with members of the chapters in Copenhagen and Roskilde, and in 1544 the turn came to the chapter in Lund. The result of these discussions was that the canons signed the three theses. In my words the text ofthe preface runs as follows: Now as in former times many people expound the Holy Writ as they please. The door to do this has been opened by Luther, and many people have followed him. Shall it be so easy to upset the long practise ofChristendom? A child or a swineherd may now discuss with a scholar, but the discussion will turn out as might be expected. Has the world been improved by the immensely learned tanners, shoemakers or dung-cart drivers? It is to be feared that it has worsened. The Lutherans neither agree with other Lutherans nor with themselves. Luther may say that the disagreement is caused by the papists, but the opposite is the case: If Luther and his followers had not sqandered the unity of the Church, there would have been but one teaching everywhere as there had been before. A few examples of the unsteadiness ofthe Lutherans: Twice or more the Lutheran bishops have changed their teaching about the Lord’s Supper. The confession they have altered over and over again, and the same applies to the baptismal ritual. These contentious changes take place with the permission of God in order to test our firmness, or they are God’s punishment for our unsteady pride. It is safer to stay with the papists than to follow these windmills. The erudite Doctors and Masters of Arts in Copenhagen want their theses discussed and signed by us, but they have to get them approved beforehand by the four principal universities and by a Christian council. The above-mentioned may seem to have been said with hard, hot-tempered words, but it is a well-intentioned guidance of His Majesty. We fear that God will punish us and His Majesty ifwe do not warn His Majesty. Before my study ofthe preface is carried out, I explain what philologists have written about style and language in Poul Helgesen’s books. In the following passages the above-mentioned comparisons are carried out. I arrive at the conclusion that there are many indications that this counter-reformation text of 1544 was written by Poul Helgesen. In a passage I discuss a number of objections that might be raised against my conclusion. Finally I describe and discuss what a number of historians and church historians have written about Poul Helgesen’s last lifetime and death.